Modelado de compensadores automáticos de potencia reactiva en lenguaje de programación dpl y dsl para la interconexión Ecuador-Perú 500 kv. - Guaman Apolo, Diana Jennifer (2022)
The interconnection of electrical systems increases the robustness of the network; however, there is a risk that, in the event of disturbances or contingencies in one of the systems, the voltage stability of the other system may be compromised. In this work, three models of compensators are studied: SVC, STATCOM, and TCSC, to regulate the voltage profile and the effect they would have on the Ecuador-Peru 500 kV Interconnection when implemented. For this purpose, the DIgSILENT PowerFactory tool is used, which allows analyzing the behavior of these devices under load variation and short-circuit scenarios.